Nilai-nilai Pendidikan Karakter dalam Novel Nazar-nazar Jiwa Karya Budi Sulistiyo En-Nafi’ - Susanti, Marlina; Hamidin, Hamidin; Nst., M. Ismail (Universitas Negeri Padang, 2013)
The aim of this research is to describe the educational character values which are consist of: (1) religious value, (2) honesty value, (3) tolerance value, (4) hard working value, (5) creativity value, (6) independent value, (7) curiousity value, (8) friendship/communicative value, (9) peacefully value, (10) fond of reading value, (11) social value, (12) responsibility value of educational character in Nazar-Nazar Jiwa novel written by Budi Sulistyo En-Nafi’. The research method is qualitative with descriptive methode. The collection of data use reading, comprehending novel as whole and making note methode which are related to educational character value. The result of this research is educational character value in Nazar-Nazar Jiwa novel written by Budi Sulistyo En-Nafi’.